Comparison of dynamic mechanical properties of dentin between deciduous and permanent teeth. (4th July 2021) - Yi, Qiao; Feng, Xiaoyu; Zhang, Chunmei; Wang, Xiumei; Wu, Xiaoshan; Wang, Jingsong; Cui, Fuzhai; Wang, Songlin
ABSTRACT: Purpose : Even though differences between deciduous and permanent dentin have been widely studied, their dynamic mechanical behavior has never been compared. The objective of the present study was to quantify the differences between deciduous and permanent dentin under cyclic mechanical loading, which is similar to masticatory stress. Materials and Methods : Deciduous and permanent teeth, respectively from children (9 ~ 12 years old) and young people (18 ~ 25 years old), were wet-sectioned perpendicular to the longitudinal axis and the central specimens of coronal dentin were evaluated by nanoscopic dynamic mechanical analysis (nanoDMA). Results : The average storage, loss, and complex moduli, as well as the hardness of deciduous dentin were signiﬁcantly (p < 0.05) lower than those of permanent dentin. Moreover, the tan δ value of permanent dentin was significantly (p < 0.05) lower than that of deciduous dentin across the loading frequency range, indicating that viscoelastic behavior and loss of elastic energy were significantly reduced in the stiffer permanent dentin. All the nanoDMA responses showed a significant influence of the dynamic loading frequency (p < 0.05): Both deciduous and permanent dentin showed reduced viscoelasticty with increased loading frequencies. Conclusions : Compared with deciduous dentin, permanent dentin exhibits higher stiffness with reduced energy loss during deformation, and therefore superior mechanical characteristics for the mastication process.